Design and manufacture of a customized, large-size and high-strength bioactive HA osteoid composite ceramic by stereolithography. Issue 7 (1st April 2023) - Liu, Ke; Wu, Xiaopei; Liu, Jiawei; Yang, He; Li, Meng; Qiu, Tong; Dai, Honglian
Abstract: Stereolithography (SLA) ceramic printing is still a challenge to establish the adaptability between printing parameters and curing properties, and to meet large-size, high mechanical and good biological properties through structural optimization. In this study, a 3D printed ceramic scaffold with a customized, large-size and high-strength bioactive osteoid structure was achieved by SLA. The interaction effects of laser power, spot spacing, and scanning rate on the curing behaviour of HA slurry were investigated. Next, a compact shell/porous core with different volume ratios was fabricated to meet the requirement of high mechanical strength for load-bearing parts by SLA. Finally, the effect of different microchannel structural units on vascularization was explored based on a modelling algorithm. In conclusion, HA composite scaffolds with large-size, high strength and excellent biological properties were developed by using SLA ceramic printing technology. High strength and structure suitable for blood vessel growth provide a basis for bioceramic repair of large bone defects.